В двойном освещении. Комическое в романе И.А. Гончарова «Обрыв» - Михаил Отрадин (ՀՀ ԳԱԱ հրատ.)
Այս ստեղծագործության առանձնահատկությունն այն է, որ գլխավոր հերոսը՝ Բորիս Ռայսկին, և «Անդունդի» հեղինակը գրում են իրենց նովելները նույն նյութի հիման վրա, նույն հերոսների մասին: Պատմելու առարկայնությունը կարևոր տարր է, որը ստեղծում է գեղարվեստական աշխարհը: The originality of this work lies in the fact that the main hero Boris Raisky and the author of “The Precipice” write their novels on the same materials, about the same heroes. The subjectification of the narration is the most important element, due to which this artistic world is created.
Keywords: Language and Literature